Soil fertility and yield of ‘Paluma’ guava fertilized with phosphorus, cattle manure, and boron - Gaudêncio P. dos Santos; Walter E. Pereira; Rosiane de L. S. de Lima; José F. de Brito Neto; Bruno de O. Dias; Thiago J. Dias (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The low soil fertility associated with the lack of adequate irrigation management are factors that most limit crop production. Therefore, the study aimed to evaluate the chemical attributes of an Oxisol and the yield of ‘Paluma’ guava under irrigation with saline water and fertilized with phosphorus, cattle manure, and boron. The treatments were distributed in randomized blocks, with four repetitions and two plants per plot, including borders on the sides of the useful experimental area, arranged in a factorial scheme (5 × 2) + 1, referring to five phosphorus doses (0, 0.08, 0.16, 0.24 and 0.32 kg of P2O5 plant-1), two doses of cattle manure, 0 and 30 kg per plant and an additional treatment consisting of 0.16 kg of P2O5 plus 30 kg of cattle manure and 1.0 g of boron, using as source the borax. In the soil, pH, phosphorus, potassium, calcium, magnesium, and the cation exchange capacity were evaluated in the 0-20 cm and 20-40 cm layers. In plants, the average yield per hectare in two harvests was estimated. The pH decreased with phosphorus doses without cattle manure and in the treatment with boron in the 20-40 cm layer. The cation exchange capacity increased with the application of phosphorus doses associated with manure and decreased in both soil layers with boron. The macronutrients evaluated were not influenced by boron. Phosphorus doses associated with cattle manure increased yield, exceeding the average of 50 t ha-1 year-1 determined for ‘Paluma’ guava. In contrast, boron did not increased the yield.